Clarification of type material for Bornean species of the genus Osteochilus (Cyprinidae) - Mcmahan, Caleb D. (Zootaxa, 2015)
Two species and one subspecies of the genus Osteochilus (Cypriniformes: Cyprinidae) were described from Borneo in a revision of the group by Karnasuta in 1993. Examination of type material has illuminated points of conflict regarding some of the type specimens listed in original descriptions. Based on archived correspondence and the author’s original thesis, we were able to determine the disposition of specimens and revise collection information for type material accordingly.